Pentingnya tanggung jawab generasi muda dalam kehidupan jemaah di Jemaah Hati Yesus Rantau Pulut - Hartoyo sulistyo putro; Maharani risa juli widiyanti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The writing of this thesis began with complaints heard from Parish Pastors, catechists and the Youth themselves (OMK) about the low value of knowledge and responsibility of young people. The aim of this thesis is to help Young Catholics (YCTH) understand their duties and responsibilities as members of the Church. In addition, this research aims to help pastors understand and identify the problems faced by young people. In problem analysis, the author uses qualitative research with a phenomenological approach. Using this phenomenological approach, the author tries to analyze and interpret the personal experiences of the informants regarding the importance of the value of responsibility of the younger generation in the life of the Hati Jesus Rantau Pulut congregation. This research uses observation, interview and documentation techniques to collect data. In this research, the author found that the majority of young Catholics in the Rantau Pulut Parish do not participate enough in church life. This is due to a lack of motivation and encouragement from parents and pastors. As a youth mobilization leader, the pastor plays an important role in leading and directing the involvement of the younger generation in church activities.